2023
DOI: 10.3390/biomedicines11051405
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Potential Impact of Quetiapine on the Microglial Trajectory and Inflammatory Response in Organotypic Cortical Cultures Derived from Rat Offspring

Abstract: Atypical antipsychotics currently constitute the first-line medication for schizophrenia, with quetiapine being one of the most commonly prescribed representatives of the group. Along with its specific affinity for multiple receptors, this compound exerts other biological characteristics, among which anti-inflammatory effects are strongly suggested. Simultaneously, published data indicated that inflammation and microglial activation could be diminished by stimulation of the CD200 receptor (CD200R), which takes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 86 publications
3
5
0
Order By: Relevance
“…As previously reported [58], exposure to the bacterial endotoxin significantly reduced the mRNA levels of Cx3cr1 in both control (p = 0.0058) and MIA (p = 0.0106) OCCs. qRT-PCR analyses revealed that the addition of aripiprazole at a dose of 100 µM to control OCCs resulted in upregulated expression of both Cx3cr1 (p = 0.0054) and Cx3cl1 (p = 0.0229).…”
Section: Effect Of Aripiprazole and Risperidone On Gene Expression Of...supporting
confidence: 85%
See 4 more Smart Citations
“…As previously reported [58], exposure to the bacterial endotoxin significantly reduced the mRNA levels of Cx3cr1 in both control (p = 0.0058) and MIA (p = 0.0106) OCCs. qRT-PCR analyses revealed that the addition of aripiprazole at a dose of 100 µM to control OCCs resulted in upregulated expression of both Cx3cr1 (p = 0.0054) and Cx3cl1 (p = 0.0229).…”
Section: Effect Of Aripiprazole and Risperidone On Gene Expression Of...supporting
confidence: 85%
“…Thirty minutes following the last medium change, control and MIA OCCs were stimulated with either aripiprazole or risperidone for 2 h and later additionally exposed to LPS for 24 h [ 57 , 58 , 59 ]. Control groups in both types of OCCs were subjected to the appropriate vehicle in the analogous volume and regimen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations